Magnitude and driving factors of boron depletion in agricultural soils - Eyherabide, Mercedes; Wyngaard, Nicolás; Larrea, Gaston Emiliano; Angelini, Hernán Pablo; Martinez Cuesta, Nicolás; Barbieri, Pablo; Reussi Calvo, Nahuel Ignacio; Sainz Rozas, Hernan Rene (Wiley, 2024)
Background: Neither the magnitude of boron (B) depletion in agricultural soils nor the driving factors of this process have been systematically studied before. Aims: The objectives of our study were to survey the extractable B (Be) in pristine soils as compared with cultivated soils, to estimate the yearly B depletion rate in agroecosystems, and to identify the edaphic, productive, and/or climatic factors determining that rate. Methods: Surface soil samples (0–20 cm layer) were taken from uncropped (UC) sites and nearby agricultural fields in 2011 and 2018 (AGR2011 and AGR2018, respectively) from the Argentinean Pampas. In these samples, Be and other edaphoclimatic and productive variables were determined, such as clay content, precipitation (PP), pH, evapotranspiration (ET), soil organic matter (SOM), and B removal with crop grains (RB). Results: The Be concentration decreased with agricultural activity, because UC soils had an average Be value of 1.9 mg kg−1, whereas AGR2011 and AGR2018 soils had values of 1.3 and 0.9 mg kg−1, respectively. The depletion rate from 2018 to 2011 ranged from 0.01 to 0.06 mg kg−1 y−1, and the main factors associated with this process were RB, PP, soil acidification, and SOM depletion (promoting B depletion) and ET and clay (reducing depletion). Conclusion: At current rates, B depletion from these agricultural soils could compromise B availability for crops in the short-to-medium term, depending on regional differences caused by edaphoclimatic and productive differences (RB, PP, pH, SOM, ET, and clay). Urgent actions are required to halt and/or revert this soil degradation process